Evolution of full-length genomes of HBV quasispecies in sera of patients with a coexistence of HBsAg and anti-HBs antibodies - Tai-Cheng Zhou (Nature Portfolio, 2017)
Abstract Although the evolutionary changes of viral quasispecies are correlated to the pathological status of a disease, little is known in the coexistence of hepatitis B surface antigen (HBsAg) and antibodies to these antigens (anti-HBs). To examine evolutionary changes in hepatitis B virus (HBV) and their relationship to the coexistence of HBsAg and anti-HBs antibodies, HBV genomes in patients with a coexistence of HBsAg and anti-HBs antibodies (experimental group) and HBsAg positive without anti-HBs (control group) were assessed. Our results showed that quasispecies diversity was significantly higher in the experimental group for large HBsAg (LHBsAg), middle HBsAg (MHBsAg), and HBsAg genes. LHBsAg harbored dN/dS values eight times higher in the experimental group; however, the mean dN/dS ratios in genes HbxAg, Pol and PreC/C of the experimental patients had an opposite trend. Phylogenetic trees in the experimental group were more complex than the control group. More positive selection sites, mutations and deletions were observed in the experimental group in specific regions. Furthermore, several amino acid variants in epitopes were potentially associated with the immune evasion. In conclusion, cumulative evolutionary changes in HBV genome that facilitate immune evasion provide insights into the genetic mechanism of a coexistence of HBsAg and anti-HBs antibodies.